PENGGUNAAN MEDIA GAMBAR DALAM MENINGKATKAN PEMAHAMAN PEMBELAJARAN MATERI ORGAN PERNAPASAN MANUSIA PADA SISWA KELAS V SEMESTER 2 SD NEGERI 5 SUMBEREJO KECAMATAN KEMILING KOTA BANDAR LAMPUNG - Mulyati, Mulyati (LPPM STKIP PGRI Bandar Lampung, 2015)
In the development of this fast growing age, learning science is very important because in essence IPA is a product of the process and its implementation (technology), including the attitudes and values contained therein. Many people argue that mastering science is very important, because in science learning students are given the opportunity and provision for processing IPA and apply it in everyday life by the way - the right way and follow the ethics of science and ethics in society. The purpose of this research is to describe the use of media images in improving the understanding of human respiratory organs learning materials in class V SDN 5 Sumberejo the 2nd half.The method used is a Classroom Action Research by using two cycles. While the subjects were students in grade 5. Data was collected with the scale of observation / observation and data analysis techniques performed by cycle analysis.Obtaining results of this study are pre-cycle value that is equal to 25.9%. This is due to not using media images. Nilau acquisition of the first cycle, which amounted to 59.26%. This is already using media images using varied methods. Cycle II acquisition value, amounting to 96.3%. This is already given the material by using media images. Based on the acquisition value is always increasing, we can conclude that the use of media images can improve student learning outcomes.